Productivity and Size of the Export Market Evidence for West and East German Plants, 2004 - Joachim Wagner (Max Planck Institute of Economics, 2007)
Using unique recently released nationally representative high-quality data at the plant level, this paper presents the first comprehensive evidence on the relationship between productivity and size of the export market for Germany, a leading actor on the world market for manufactured goods. It documents that firms that export to countries inside the euro-zone are more productive than firms that sell their products in Germany only, but less productive than firms that export to countries outside the euro-zone, too. This is in line with the hypothesis that export markets outside the euro-zone have higher entry costs that can only by paid by more productive firms.
Keywords: F14; D21; 330; Exports; productivity; micro data; Germany; Exportindustrie; Produktivität; Industriegüteraußenhandel; Auslandsmarkt; Landesgröße; Deutschland; EU-Staaten; Welt